1986
DOI: 10.1161/01.str.17.6.1313
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral performance of rats following neonatal hypoxia-ischemia.

Abstract: The behavioral performance of rats subjected in the neonatal period to hypoxia-ischemia at either 37 degrees C or 21 degrees C was compared to that of sham-ligated animals. Performance on complex motor tests was significantly delayed only in the hypoxic-ischemic 37 degrees C rats. However, cognitive testing disclosed significant delay of spatial learning in animals subjected to hypoxia-ischemia at 21 degrees C and those with gross infarction at 37 degrees C. There was enhanced avoidance learning in the animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 16 publications
3
29
0
2
Order By: Relevance
“…Previous studies have found that HI causes a number of functional deficits including slowing of various developmental milestones (eye opening, righting reflex), locomotor activity and sensorimotor and memory deficits (24,25,28,29). The present study used three different functional indices to assess behavioral deficits after HI and of these, the grip traction test which is used to assess forelimb muscle strength, appeared to be the most useful index relating to total lesion volume.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have found that HI causes a number of functional deficits including slowing of various developmental milestones (eye opening, righting reflex), locomotor activity and sensorimotor and memory deficits (24,25,28,29). The present study used three different functional indices to assess behavioral deficits after HI and of these, the grip traction test which is used to assess forelimb muscle strength, appeared to be the most useful index relating to total lesion volume.…”
Section: Discussionmentioning
confidence: 77%
“…Immediately after hypoxic exposure pups were exposed either to RA or 100% O 2 for 30 min at 25°C and then returned to their dams. Because it has been shown that carotid artery ligation without hypoxia (sham) produced neither brain damage, nor functional impairments in rodents (13,14), littermate naïve (no HI) mice were used as a control. Mice that died during hypoxia (n ϭ 8) or cannibalized (n ϭ 11) by their dams were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…We refrained from evaluating an additional group of animals with carotid artery ligation only, inasmuch as it has been demonstrated that ligation neither produced brain damage (22) nor functional impairments (13,28,29). A total of 62 rats were used in the experiment.…”
Section: Methodsmentioning
confidence: 99%